Quantitative assessment of renal functions using 68Ga-EDTA dynamic PET imaging in renal injury in mice of different origins - Ding, Ying; Liu, Yu; Zhang, Li; Deng, Yinqian; Chen, Huanyu; Lan, Xiaoli; Jiang, Dawei; Cao, Wei (Frontiers in Medicine, 2023)
Background: Kidney dysfunction often stays silent at its onset and blood test or traditional imaging methods (CT, MRI, or ultrasonography) prove suboptimal in renal function evaluation. Single photon emission computed tomography (SPECT) renal scan can measure glomerular filtration rates (GFR), but its planar imaging modality and semi-quantification limit diagnostic accuracy for a variety of patients. Herein, a PET tracer 68Ga-EDTA is prepared with the aim of measuring split GFR and we comprehensively investigate its performance in murine models of kidney dysfunction. Methods: 68Ga-EDTA dynamic PET scanning was performed on healthy C57BL/6 mice and renal injury models, including acute kidney injury (AKI) and unilateral ureter obstruction (UUO). 68Ga-EDTA PET image and time-radioactivity curve (TAC) were acquired through the 30 min dynamic scanning. Renal function and GFR value were measured using renograms and systematically verified with serum renal function parameters, biodistribution results, and pathological staining. Results: 68Ga-EDTA dynamic PET scanning quantitatively presented the process of tracer elimination. The calculated GFR using dynamic PET of healthy mice is 0.25±0.02 mL/min, 0.01±0.00 mL/min for AKI mice, and 0.25±0.04, 0.29±0.03, and 0.24±0.01 mL/min for UUO mice after different days after the operation. Furthermore, 68Ga-EDTA dynamic PET imaging and GFRPET can differentiate mildly impaired kidney function before serum parameters become obvious. Conclusions: 68Ga-EDTA dynamic PET delivers on expectations of early and precise renal function evaluation in two kidney injury models. We believe our results pave the path for wide clinical application of 68Ga-EDTA dynamic PET in the coming years.